2023
DOI: 10.1021/acs.energyfuels.2c03502
|View full text |Cite
|
Sign up to set email alerts
|

CuInS2 Nanosheet Arrays with a MoS2 Heterojunction as a Photocathode for PEC Water Splitting

Abstract: Developing cost-effective noble metal-free co-catalysts as alternatives to platinum group metals is an impeccable strategy to enhance photoelectrochemical (PEC) water splitting. In this report, we successfully fabricated CuInS2 nanosheet array-based photocathode modified with CdS and co-catalyst MoS2 in a green approach to improve water splitting under solar irradiation. The visible light absorption of the modified hybrid photocathode (CIS/CdS/MoS2) was significantly enhanced due to introducing CdS and MoS2. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The high-resolution deconvoluted XPS of Bi 4f (Figure b) shows two peaks at 158.7 and 164.0 eV, corresponding to Bi 4f 5/2 and Bi 4f 7/2 , respectively, which are typical of Bi 3+ species. Figure c shows the XPS spectra of Cu 2p with the featured binding energies of 934.1 and 954.0 eV corresponding to Cu 2p 3/2 and Cu 2p 1/2 respectively . The asymmetric profile of O 1s can be split into two symmetrical peaks at 529.6 and 531.8 eV (Figure d), indicating lattice oxygen in CBO and chemisorbed oxygen (OH) on the surface, respectively .…”
Section: Resultsmentioning
confidence: 98%
“…The high-resolution deconvoluted XPS of Bi 4f (Figure b) shows two peaks at 158.7 and 164.0 eV, corresponding to Bi 4f 5/2 and Bi 4f 7/2 , respectively, which are typical of Bi 3+ species. Figure c shows the XPS spectra of Cu 2p with the featured binding energies of 934.1 and 954.0 eV corresponding to Cu 2p 3/2 and Cu 2p 1/2 respectively . The asymmetric profile of O 1s can be split into two symmetrical peaks at 529.6 and 531.8 eV (Figure d), indicating lattice oxygen in CBO and chemisorbed oxygen (OH) on the surface, respectively .…”
Section: Resultsmentioning
confidence: 98%
“…34,35 Among them, the CuBi 2 O 4 (CBO) material can be recognized as one of the promising candidates for the photoelectrode material for the PEC HER involving CO 2 reduction. [36][37][38][39][40][41][42][43][44][45][46][47][48] CBO has a tetragonal crystal structure and consists of stacks of square planar Cu(II)O 4 groups linked to distorted trigonal Bi(III)O 6 polyhedral groups. 34 The bandgap (E g ) energy of the CBO material has been reported to be 1.5-1.8 eV (adsorption edge wavelength up to 830 nm), 37,38,42,44 which leads to a theoretical STH energy conversion efficiency limit of B24% at an external quantum efficiency (EQE) of 100%.…”
Section: Introductionmentioning
confidence: 99%
“…These light-absorption features, theoretically expected PEC performances, and an energy level alignment with the standard redox potential of the HER have promoted advanced research for CBO-based photocathodes involving a PEC cell for nonbiased overall water splitting. 36,[48][49][50][51] Wang et al have reported that the CBO-based photoelectrode prepared through a spray pyrolysis method produces a photocurrent density of À2.0 mA cm À2 at 0.6 V RHE in the presence of an H 2 O 2 sacrificial reagent. 41 In addition, À2.66 mA cm À2 at 0.6 V RHE generated by the optimized CBO photoelectrodes has been established by Xu et al 47 Non-biased overall water splitting by a PEC cell with a combination of photoanodes for the OER such as TiO 2 , BiVO 4 , and ZnIn 2 S 4 has been investigated, but typically exhibits an STH energy conversion efficiency of less than 1.0%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations